Evaluation of SCEC CyberShake Ground Motions for Engineering Practice. Issue 3 (August 2019) - Teng, Ganyu; Baker, Jack
This paper evaluates CyberShake (version 15.12) ground motions for potential application to high-rise building design in the Los Angeles region by comparing them against recordings from past earthquakes as well as empirical models. We consider two selected sites in the Los Angeles region with different underlying soil conditions and select comparable suites of ground motion records from CyberShake and the NGA-West2 database according to the ASCE 7-16 requirements. Major observations include (1) selected ground motions from CyberShake and NGA-West2 share similar features, in terms of response spectra and polarization; (2) when selecting records from Cyber-Shake, it is easy to select motions with sources that match the hazard deaggregation; (3) CyberShake durations on soil are consistent with the empirical models considered, whereas durations on rock are slightly shorter; (4) occasional excessive polarization in ground motion is produced by San Andreas fault ruptures, though those records are usually excluded after the ground motion selection. Results from this study suggest that CyberShake ground motions are a suitable and promising source of ground motions for engineering evaluations.